Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Hasil Belajar IPA Peserta Didik Kelas VII - Maarifuddin, Maarifuddin; Nugraheni, Diah; Winarni, Dyah Setyaningrum (Manalisih: Jurnal Penelitian, Sosial, dan Humaniora; Vol 1 No 1 (2023): Manalisih: Jurnal Penelitian, Sosial, dan Humaniora, 2023)
The teacher as a driving force for the learning process, especially in the scope of the school, has an important role in supporting the success of students. The teacher must be able to choose a learning model that suits the characteristics of the subject, for example Natural Sciences. The science subjects contain many factual things and require a learning model in order to stimulate and encourage students to carry out activities in achieving the maximum potential they have individually or in groups. One learning model that is able to overcome the learning problem is to use the Jigsaw type cooperative learning model. This study aims to find out whether there is an influence of the Jigsaw type cooperative learning model on the learning outcomes of the science of students in grade VII SMP IT. The approach used in this study is a quantitative approach. The method used is the quasi-experimental method. The research design used is Non-Randomize Control Group Pretest and Posttest Design. The population in this study were students of class VII of the 2022/2023 school year. The sample used in this study consisted of 2 classes, namely 25 students in class VII B (experimental class) and 25 students of class VII A (control class). The sampling technique used in this study is purposive sampling. The data obtained were analyzed using the Independent Sample T-Test. The results of the study showed the influence of the Jigsaw type cooperative learning model on the learning outcomes of the IT Junior High School students in Secang.